Positive electrode for nonaqueous electrolyte power storage element, method of manufacturing positive electrode for nonaqueous electrolyte power storage element, and nonaqueous electrolyte power storage element

JP2025034927APending Publication Date: 2025-03-13GS YUASA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023141609
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0011】 本発明の一側面によれば、充放電サイクル後の直流抵抗の増加率を低減することができる非水電解質蓄電素子用正極及びその製造方法、並びに充放電サイクル後の直流抵抗の増加率が低減されている非水電解質蓄電素子を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034927000001_ABST
    Figure 2025034927000001_ABST
Patent Text Reader

Abstract

To provide a positive electrode for nonaqueous electrolyte power storage elements and a method of manufacturing the same, capable of reducing an increase rate of DC resistance after charge / discharge cycles, and a nonaqueous electrolyte power storage element reduced in increase rate of DC resistance after charge / discharge cycles.SOLUTION: A positive electrode for nonaqueous electrolyte power storage elements according to an aspect of the present invention includes a positive electrode active material layer that contains: a positive electrode active material containing a lithium transition metal composite oxide; and fibrous carbon. The lithium transition metal composite oxide contains at least one element selected from the group consisting of a nickel element, a cobalt element and a manganese element. A content of the nickel element relative to all of metal elements other than a lithium element in the lithium transition metal composite oxide is less than 80 mol%, and a content of lithium hydroxide contained in the positive electrode active material is 0.20 mass% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode for a nonaqueous electrolyte storage element, a method for producing a positive electrode for a nonaqueous electrolyte storage element, and a nonaqueous electrolyte storage element. [Background technology]

[0002] Non-aqueous electrolyte secondary batteries, such as lithium ion secondary batteries, are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. Non-aqueous electrolyte secondary batteries generally have a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and are configured to charge and discharge by transferring charge-transporting ions between the electrodes. As non-aqueous electrolyte storage elements other than non-aqueous electrolyte secondary batteries, capacitors such as lithium ion capacitors and electric double layer capacitors are also widely used.

[0003] Conventionally, lithium transition metal composite oxides having an α-NaFeO2 type crystal structure have been considered as positive electrode active materials for non-aqueous electrolyte storage elements, and LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and the like have been developed and put into practical use (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2015-18678 A [Patent Document 2] International Publication No. 2019 / 088171 Summary of the Invention [Problem to be solved by the invention]

[0005] Conventional positive electrodes for non-aqueous electrolyte electricity storage elements and electricity storage elements using lithium transition metal composite oxides have the disadvantage that direct current resistance is likely to increase with charge / discharge cycles.

[0006] An object of the present invention is to provide a positive electrode for a nonaqueous electrolyte storage element that can reduce the rate of increase in DC resistance after charge-discharge cycles, a method for producing the same, and a nonaqueous electrolyte storage element in which the rate of increase in DC resistance after charge-discharge cycles is reduced. [Means for solving the problem]

[0007] A positive electrode for a nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode active material layer containing fibrous carbon and a positive electrode active material including a lithium transition metal composite oxide, the lithium transition metal composite oxide containing at least one element selected from the group consisting of nickel, cobalt and manganese, the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %, and the content of lithium hydroxide contained in the positive electrode active material is 0.20 mass % or less.

[0008] A positive electrode for a nonaqueous electrolyte storage element according to another aspect of the present invention comprises a positive electrode active material layer containing fibrous carbon and a positive electrode active material including a lithium transition metal composite oxide, the lithium transition metal composite oxide containing at least one element selected from the group consisting of nickel, cobalt and manganese, the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %, and the content of lithium hydroxide in the positive electrode active material layer is 0.20 mass % or less.

[0009] A method for producing a positive electrode for a non-aqueous electrolyte storage element according to another aspect of the present invention includes preparing a positive electrode mixture paste containing a positive electrode active material including a lithium transition metal composite oxide and fibrous carbon, wherein the lithium transition metal composite oxide contains at least one element selected from the group consisting of nickel, cobalt, and manganese, the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %, and the content of lithium hydroxide contained in the positive electrode active material is 0.20 mass % or less.

[0010] A nonaqueous electrolyte storage element according to another aspect of the present invention includes the positive electrode for the nonaqueous electrolyte storage element according to the aspect of the present invention. Effect of the Invention

[0011] According to one aspect of the present invention, it is possible to provide a positive electrode for a nonaqueous electrolyte storage element that can reduce the rate of increase in DC resistance after charge-discharge cycles, a method for producing the same, and a nonaqueous electrolyte storage element in which the rate of increase in DC resistance after charge-discharge cycles is reduced. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a perspective view showing one embodiment of a nonaqueous electrolyte electricity storage element. [Diagram 2] FIG. 2 is a schematic diagram showing one embodiment of an electricity storage device formed by assembling a plurality of nonaqueous electrolyte electricity storage elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] First, an overview of the positive electrode for a nonaqueous electrolyte storage element, the method for producing the positive electrode for a nonaqueous electrolyte storage element, and the nonaqueous electrolyte storage element disclosed in this specification will be described.

[0014] [1] A positive electrode for a nonaqueous electrolyte storage element according to one aspect of the present invention comprises a positive electrode active material layer containing fibrous carbon and a positive electrode active material including a lithium transition metal composite oxide, the lithium transition metal composite oxide containing at least one element selected from the group consisting of nickel, cobalt, and manganese, the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %, and the content of lithium hydroxide contained in the positive electrode active material is 0.20 mass % or less.

[0015] The positive electrode for a non-aqueous electrolyte storage element described in [1] above can reduce the rate of increase in direct current resistance after charge / discharge cycles. The reason for this is unclear, but the following reasons are presumed. By using fibrous carbon as a conductive agent, the electron conduction path in the positive electrode active material layer tends to be sufficiently formed. However, if lithium hydroxide is present on the surface of the positive electrode active material, the contact between the positive electrode active material and the fibrous carbon is easily hindered, and the electron conduction path is easily cut off with charge / discharge cycles. In particular, a lithium transition metal composite oxide containing at least one selected from the group consisting of nickel, cobalt, and manganese elements, and having a nickel content of less than 80 mol% relative to all metal elements other than lithium in the lithium transition metal composite oxide, has a large volume change due to expansion and contraction with charge / discharge, so contact with the conductive agent is important. Therefore, by reducing the content of lithium hydroxide in a positive electrode using such a positive electrode active material, the contact between the positive electrode active material and the fibrous carbon is strong, and the electron conduction path is easily maintained even when the charge / discharge cycle is repeated. In addition, in a lithium transition metal composite oxide containing at least one selected from the group consisting of nickel, cobalt, and manganese, and in which the content of nickel relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol%, even when the lithium hydroxide content is reduced, the crystal structure is unlikely to change and good performance can be exhibited. For these reasons, it is presumed that the positive electrode for a nonaqueous electrolyte storage element described in [1] above can reduce the rate of increase in DC resistance after charge-discharge cycles.

[0016] "Fibrous carbon" refers to a fibrous carbon material. A carbon material refers to a material in which the main element (the element with the highest content by mass) is carbon. The content of carbon element in the carbon material is, for example, 70 mass% or more, preferably 90 mass% or more, and more preferably 95 mass% or more. Examples of elements other than carbon element that may be contained in the carbon material include oxygen element and hydrogen element. Fibrous refers to a deformable elongated shape. The aspect ratio of the fibrous carbon (ratio of length to diameter (fiber diameter)) is, for example, 10 or more, preferably 100 or more, and more preferably 1,000 or more. The diameter and length of the fibrous carbon are determined based on a scanning electron microscope (SEM) or transmission electron microscope (TEM) image of a cross-section of the positive electrode active material layer, as described below.

[0017] The elemental composition ratio of the lithium transition metal composite oxide is the elemental composition ratio in the lithium transition metal composite oxide before charging and discharging, or, in the case of the lithium transition metal composite oxide contained in the positive electrode of the nonaqueous electrolyte storage element, the elemental composition ratio in a fully discharged state treated by the following procedure. First, the nonaqueous electrolyte storage element is charged at a constant current of 0.05 C until the charge end voltage in normal use is reached, and the elemental composition ratio is fully charged. After a 30-minute rest, the elemental electrolyte storage element is discharged at a constant current of 0.05 C until the discharge end voltage in normal use is reached. The elemental electrolyte storage element is disassembled, the positive electrode is removed, and a test battery is assembled with the removed positive electrode as the working electrode and a metallic lithium electrode as the counter electrode. Pure metallic lithium is used for the metallic lithium electrode here. The test battery is charged at a current of 10 mA per 1 g of positive electrode active material until the positive electrode potential reaches 2.0 V (vs. Li / Li +) to adjust the positive electrode to a fully discharged state. The positive electrode is disassembled again and the positive electrode is taken out. The non-aqueous electrolyte attached to the taken-out positive electrode is thoroughly washed using dimethyl carbonate, and the positive electrode is dried under reduced pressure at room temperature for 24 hours, after which the lithium transition metal composite oxide of the positive electrode active material is taken out. The taken-out lithium transition metal composite oxide is subjected to measurement. The operations from disassembling the non-aqueous electrolyte storage element to taking out the lithium transition metal composite oxide are carried out in an argon atmosphere with a dew point of -60°C or less. "During normal use" refers to the case where the non-aqueous electrolyte storage element is used under charge and discharge conditions recommended or specified for the non-aqueous electrolyte storage element, and in the case where equipment for using the non-aqueous electrolyte storage element is prepared, the equipment is used to use the non-aqueous electrolyte storage element.

[0018] The content of lithium hydroxide contained in the positive electrode active material is determined by fully discharging the positive electrode by the above method, collecting the positive electrode active material from the positive electrode after washing, dispersing the positive electrode active material in water to dissolve the water-soluble lithium salt contained in the positive electrode active material in water, and using a titration method according to the reaction formulas shown in the following formulas (1) to (3). Specifically, first, the total content of lithium hydroxide and lithium carbonate in the lithium salt is quantified from the first neutralization point observed based on the following formulas (1) and (2), and then the content of lithium carbonate in the lithium salt is quantified from the second neutralization point observed based on the following formula (3). The difference between the total content of lithium hydroxide and lithium carbonate and the content of lithium carbonate is defined as the content of lithium hydroxide. The content of lithium hydroxide contained in the positive electrode active material layer described below is determined by fully discharging the positive electrode using the above method, washing the positive electrode, extracting the positive electrode active material layer from the positive electrode, dispersing the positive electrode active material layer in water to dissolve the water-soluble lithium salt contained in the positive electrode active material layer in water, and then repeating the above method. The process from extracting the positive electrode active material or the positive electrode active material layer to dispersing it in water is performed in an environment where LiOH does not change into other compounds. (1) LiOH+HCl → LiCl+H2O (2) Li2CO3+HCl → LiHCO3+LiCl (3) LiHCO3+HCl → LiCl+H2O+CO2

[0019] [2] A positive electrode for a nonaqueous electrolyte storage element according to another aspect of the present invention comprises a positive electrode active material layer containing fibrous carbon and a positive electrode active material including a lithium transition metal complex oxide, the lithium transition metal complex oxide containing at least one element selected from the group consisting of nickel, cobalt and manganese, the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal complex oxide is less than 80 mol %, and the content of lithium hydroxide in the positive electrode active material layer is 0.20 mass % or less.

[0020] The positive electrode for a non-aqueous electrolyte storage element described in [2] above can reduce the rate of increase in direct current resistance after charge-discharge cycles. The reason for this is unclear, but it is presumed to be the same as that for the positive electrode for a non-aqueous electrolyte storage element described in [1] above. The positive electrode for a non-aqueous electrolyte storage element described in [1] above is different in that the content of lithium hydroxide is based on the positive electrode active material, whereas the positive electrode for a non-aqueous electrolyte storage element described in [2] above is different in that the content of lithium hydroxide is based on the positive electrode active material layer.

[0021] [3] A method for producing a positive electrode for a non-aqueous electrolyte storage element according to another aspect of the present invention includes preparing a positive electrode mixture paste containing a positive electrode active material including a lithium transition metal composite oxide and fibrous carbon, wherein the lithium transition metal composite oxide contains at least one element selected from the group consisting of nickel, cobalt, and manganese, the content of the nickel in the lithium transition metal composite oxide relative to all metal elements other than lithium is less than 80 mol %, and the content of lithium hydroxide in the positive electrode active material is 0.20 mass % or less.

[0022] The method for producing a positive electrode for a nonaqueous electrolyte storage element described in the above item [3] can produce a positive electrode for a nonaqueous electrolyte storage element that can reduce the rate of increase in DC resistance after charge-discharge cycles.

[0023] [4] A nonaqueous electrolyte storage element according to another aspect of the present invention includes the positive electrode for a nonaqueous electrolyte storage element according to [1] or [2] above.

[0024] The nonaqueous electrolyte storage element described in [4] above includes the positive electrode for a nonaqueous electrolyte storage element described in [1] or [2] above, and therefore has a reduced rate of increase in direct current resistance after charge-discharge cycles.

[0025] A positive electrode for a nonaqueous electrolyte storage element according to one embodiment of the present invention, a method for manufacturing a positive electrode for a nonaqueous electrolyte storage element, a nonaqueous electrolyte storage element, an electricity storage device, a method for manufacturing a nonaqueous electrolyte storage element, and other embodiments will be described in detail. Note that the names of the components (components) used in each embodiment may differ from the names of the components (components) used in the background art.

[0026] <Positive electrode for non-aqueous electrolyte storage element> A positive electrode for a non-aqueous electrolyte storage element according to one embodiment of the present invention (hereinafter, simply referred to as "positive electrode") has a positive electrode substrate and a positive electrode active material layer disposed on the positive electrode substrate directly or via an intermediate layer. The positive electrode is a positive electrode for a non-aqueous electrolyte storage element, preferably a positive electrode for a non-aqueous electrolyte secondary battery, and more preferably a positive electrode for a non-aqueous electrolyte secondary battery.

[0027] The positive electrode substrate is conductive. Whether or not it has "conductivity" is determined by whether the volume resistivity measured in accordance with JIS-H-0505 (1975) is 10 -2The threshold value is Ω·cm. The material of the positive electrode substrate is a metal such as aluminum, titanium, tantalum, stainless steel, or an alloy thereof. Among these, aluminum or an aluminum alloy is preferred from the viewpoints of potential resistance, high conductivity, and cost. The positive electrode substrate may be a foil, a vapor deposition film, a mesh, a porous material, etc., and a foil is preferred from the viewpoint of cost. Therefore, aluminum foil or an aluminum alloy foil is preferred as the positive electrode substrate. Examples of aluminum or an aluminum alloy include A1085, A3003, A1N30, etc., as specified in JIS-H-4000 (2014) or JIS-H-4160 (2006).

[0028] The average thickness of the positive electrode substrate is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate within the above range, it is possible to increase the strength of the positive electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0029] The intermediate layer is a layer disposed between the positive electrode substrate and the positive electrode active material layer. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0030] The positive electrode active material layer contains a positive electrode active material and fibrous carbon. The positive electrode active material layer may contain optional components other than the fibrous carbon, such as a conductive agent, a binder, a thickener, a filler, and a neutralizer, as necessary.

[0031] The positive electrode active material includes a lithium transition metal composite oxide. The lithium transition metal composite oxide includes at least one element selected from the group consisting of nickel, cobalt, and manganese, and the content of nickel in the lithium transition metal composite oxide is less than 80 mol% relative to all metal elements other than lithium. The lithium transition metal composite oxide preferably includes nickel, cobalt, and manganese.

[0032] The content (Ni / Me) of nickel element relative to all metal elements (Me) other than lithium element in the lithium transition metal composite oxide is less than 80 mol%. The upper limit of the content (Ni / Me) of the nickel element is preferably 75 mol%, more preferably 70 mol%, and even more preferably 65 mol%. The lower limit of the content (Ni / Me) of the nickel element may be 0 mol%, but is preferably 10 mol%, more preferably 30 mol%, more preferably 50 mol%, and even more preferably 55 mol%. The content (Ni / Me) of the nickel element can be a combination of any of the above lower limits and any of the above upper limits.

[0033] The content of cobalt element (Co / Me) relative to all metal elements other than lithium element (Me) in the lithium transition metal composite oxide is preferably 0 mol% or more and 50 mol% or less, more preferably 5 mol% or more and 40 mol% or less, even more preferably 10 mol% or more and 30 mol% or less, and even more preferably 15 mol% or more and 25 mol% or less.

[0034] The content of manganese element (Mn / Me) relative to all metal elements other than lithium element (Me) in the lithium transition metal composite oxide is preferably 0 mol% or more and 50 mol% or less, more preferably 5 mol% or more and 40 mol% or less, even more preferably 10 mol% or more and 30 mol% or less, and even more preferably 15 mol% or more and 25 mol% or less.

[0035] When the nickel, cobalt and manganese elements in the lithium transition metal composite oxide are within the above-mentioned content ranges, the volume change due to expansion and contraction accompanying charge and discharge is particularly large, and contact with the conductive agent becomes even more important, so that there is great technical significance in adopting the present invention.

[0036] The lithium transition metal composite oxide may further contain other transition metal elements other than nickel, cobalt and manganese, typical metal elements other than lithium such as aluminum, etc. However, the lower limit of the total content ((Ni+Co+Mn) / Me) of nickel, cobalt and manganese relative to all metal elements (Me) other than lithium in the lithium transition metal composite oxide is preferably 90 mol%, more preferably 95 mol%, and even more preferably 99 mol%. When the metal elements other than lithium in the lithium transition metal composite oxide are substantially composed only of nickel, cobalt and manganese, the volume change due to expansion and contraction accompanying charge and discharge is particularly large, and contact with the conductive agent becomes even more important, so that the technical significance of adopting the present invention is great.

[0037] The lithium transition metal composite oxide is preferably a lithium transition metal composite oxide having a layered α-NaFeO2 type crystal structure. The lithium transition metal composite oxide is preferably a compound represented by the following formula (1).

[0038] Li 1+α Me 1-α O2···(1) In the formula (1), Me is a metal element other than Li, which contains at least one selected from the group consisting of Ni, Co, and Mn, and 0≦α<1.

[0039] In formula (1), α may be 0 or more and 0.5 or less, 0 or more and 0.3 or less, or 0 or more and 0.1 or less.

[0040] In the compound represented by formula (1), the content of Ni relative to Me (Ni / Me) is less than 80 mol %. The preferred elemental composition of Me in formula (1) is the same as the preferred elemental composition of all metal elements (Me) other than lithium element in the above-mentioned lithium transition metal composite oxide.

[0041] The content of the lithium transition metal composite oxide in the positive electrode active material layer is preferably 70% by mass to 99% by mass, more preferably 80% by mass to 98% by mass, and even more preferably 90% by mass to 97% by mass. By setting the content of the lithium transition metal composite oxide in the above range, it is possible to reduce the rate of increase in DC resistance after charge / discharge cycles while achieving both high energy density and manufacturability of the positive electrode active material layer.

[0042] The positive electrode active material may contain lithium hydroxide. In the production of lithium transition metal composite oxides, lithium hydroxide is generally used as one of the raw materials. For this reason, lithium hydroxide may remain in the positive electrode active material containing the lithium transition metal composite oxide. Note that, since a part or all of the lithium hydroxide contained in the positive electrode active material may become a lithium salt other than lithium hydroxide through a neutralization reaction with a neutralizing agent described later, the positive electrode active material and the positive electrode active material layer may also contain lithium salts other than lithium hydroxide.

[0043] In one embodiment of the present invention, the upper limit of the content of lithium hydroxide contained in the positive electrode active material is 0.20% by mass, preferably 0.15% by mass, more preferably 0.12% by mass, and even more preferably 0.10% by mass. When the content of lithium hydroxide contained in the positive electrode active material is equal to or less than the above upper limit, the contact between the positive electrode active material and the fibrous carbon is strengthened, and the increase rate of the direct current resistance after the charge-discharge cycle can be reduced. The content of lithium hydroxide contained in the positive electrode active material can be adjusted by the manufacturing conditions, and for example, the content of lithium hydroxide contained in the positive electrode active material tends to be reduced by high-temperature baking. In addition, the content of lithium hydroxide contained in the positive electrode active material can be reduced by performing sufficient water washing. The lower limit of the content of lithium hydroxide contained in the positive electrode active material may be 0.00% by mass, or may be 0.01% by mass, 0.03% by mass, or 0.05% by mass. When excessive high-temperature baking or water washing is performed in order to reduce the content of lithium hydroxide, the crystal structure of the lithium transition metal composite oxide may be affected. The content of lithium hydroxide contained in the positive electrode active material can be a combination of any of the above-mentioned lower limits and any of the above-mentioned upper limits.

[0044] In another embodiment of the present invention, the upper limit of the content of lithium hydroxide contained in the positive electrode active material layer is 0.20% by mass, preferably 0.15% by mass, more preferably 0.12% by mass, and even more preferably 0.10% by mass. By the content of lithium hydroxide contained in the positive electrode active material layer being equal to or less than the above upper limit, the contact between the positive electrode active material and the fibrous carbon is strengthened, and the increase rate of the direct current resistance after the charge-discharge cycle can be reduced. The content of lithium hydroxide contained in the positive electrode active material layer can be adjusted by the manufacturing conditions of the positive electrode active material and the positive electrode active material layer. The lower limit of the content of lithium hydroxide contained in the positive electrode active material layer may be 0.00% by mass, or may be 0.01% by mass, 0.03% by mass, or 0.05% by mass. The content of lithium hydroxide contained in the positive electrode active material layer can be a combination of any of the above-mentioned lower limits and any of the above-mentioned upper limits.

[0045] The positive electrode active material may further contain other positive electrode active materials other than the lithium transition metal composite oxide. As the other positive electrode active materials, various conventionally known positive electrode active materials can be used. However, the content of the lithium transition metal composite oxide with respect to all the positive electrode active materials contained in the positive electrode active material layer is preferably 90% by mass or more, more preferably 99% by mass or more. In this way, by mainly using the lithium transition metal composite oxide as the positive electrode active material, the effect of the present invention can be particularly fully exhibited.

[0046] The positive electrode active material is usually a particle (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer is improved. In addition, when a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material. The "average particle size" means a value at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013).

[0047] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both dry and wet methods.

[0048] The content of all the positive electrode active materials in the positive electrode active material layer is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 97% by mass. By setting the content of all the positive electrode active materials within the above range, it is possible to achieve both high energy density and manufacturability of the positive electrode active material layer.

[0049] The fibrous carbon is usually a component that functions as a conductive agent. That is, the fibrous carbon is preferably conductive. Examples of the fibrous carbon include carbon fiber, pitch-based carbon fiber, and carbon nanotube (CNT), and among these, CNT is preferable. One or more types of fibrous carbon can be used.

[0050] The average diameter (average fiber diameter) of the fibrous carbon is, for example, preferably 0.5 nm or more and 10 μm or less, more preferably 1 nm or more and 1 μm or less, even more preferably 2 nm or more and 100 nm or less, even more preferably 3 nm or more and 60 nm or less, and even more preferably 4 nm or more and 40 nm or less. When the average diameter of the fibrous carbon is within the above range, the electron conductivity of the positive electrode active material layer becomes better, and the increase rate of the direct current resistance after the charge and discharge cycle can be further reduced. The "average diameter" of the fibrous carbon is the average value of the diameters of any 10 pieces of fibrous carbon observed by SEM or TEM.

[0051] The average aspect ratio of the fibrous carbon (ratio of average length to average diameter) is, for example, 10 or more, preferably 10 to 10,000, more preferably 100 or more, and even more preferably 1,000 or more. By using fibrous carbon with an average aspect ratio in the above range, the electron conductivity of the positive electrode active material layer can be improved. The "average length" of the fibrous carbon is the average value of the lengths of any 10 fibrous carbons observed by SEM or TEM. When calculating the average aspect ratio, it is preferable that the 10 fibrous carbons for obtaining the average diameter and the 10 fibrous carbons for obtaining the average length are the same fibrous carbons, but the average diameter and average length of each of the different 10 fibrous carbons may be obtained, and the ratio of the average aspect ratio may be used. That is, the average aspect ratio is the average value of each aspect ratio of any 10 fibrous carbons observed by SEM or TEM, or the ratio of the average length of any 10 different fibrous carbons to the average diameter of any 10 fibrous carbons observed by SEM or TEM.

[0052] The average lattice spacing (d 002 The average lattice spacing (d 002 When the average lattice spacing (d 002 The lower limit of the (002) peak of the fibrous carbon measured by X-ray diffraction using CuKα radiation is, for example, 0.5° or more. The (002) peak of the fibrous carbon is preferably less than 0.7°.

[0053] The fibrous carbon can be obtained by, for example, forming a polymer into a fiber form by a spinning method or the like, and then heat-treating the fiber in an inert atmosphere, or by a vapor phase growth method in which an organic compound is reacted at high temperature in the presence of a catalyst, etc. Commercially available fibrous carbon can be used.

[0054] The content of fibrous carbon in the positive electrode active material layer is preferably 0.05% by mass or more and 5.0% by mass or less, more preferably 0.1% by mass or more and 4.0% by mass or less, even more preferably 0.2% by mass or more and 3.0% by mass or less, even more preferably 0.3% by mass or more and 2.5% by mass or less, even more preferably 0.5% by mass or more and 2.0% by mass or less, and particularly preferably 0.8% by mass or more and 1.5% by mass or less. By setting the content of fibrous carbon to the above lower limit or more, the electronic conductivity of the positive electrode active material layer can be further increased and the increase rate of direct current resistance after charge and discharge cycles can be further reduced. On the other hand, by setting the content of fibrous carbon to the above upper limit or less, the increase rate of direct current resistance after charge and discharge cycles can be sufficiently reduced while relatively increasing the content of the positive electrode active material, thereby increasing the energy density, etc. In addition, by setting the content of fibrous carbon to the above upper limit or less, production costs can also be suppressed.

[0055] The content of fibrous carbon relative to the positive electrode active material (fibrous carbon / positive electrode active material) is preferably 0.05% by mass or more and 5.3% by mass or less, more preferably 0.1% by mass or more and 4.2% by mass or less, even more preferably 0.2% by mass or more and 3.2% by mass or less, even more preferably 0.3% by mass or more and 2.7% by mass or less, even more preferably 0.5% by mass or more and 2.1% by mass or less, and particularly preferably 0.8% by mass or more and 1.6% by mass or less. When the content of fibrous carbon relative to the positive electrode active material is equal to or more than the lower limit, the fibrous carbon can sufficiently cover the surface of the particles of the positive electrode active material, so that a good electron conduction path is formed, and the increase rate of the direct current resistance after the charge / discharge cycle can be further reduced. On the other hand, when the content of fibrous carbon relative to the positive electrode active material is equal to or less than the upper limit, the voids between the particles of the positive electrode active material are suppressed from being occupied by the excessive fibrous carbon, and the increase rate of the direct current resistance after the charge / discharge cycle is further reduced.

[0056] The positive electrode active material layer may further contain other conductive agents other than fibrous carbon. The other conductive agents are not particularly limited as long as they are materials other than fibrous carbon and have electrical conductivity. Examples of such conductive agents include non-fibrous carbon materials, metals, conductive ceramics, and the like. Examples of carbon materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include fullerene, and the like. Examples of the shape of the other conductive agents include powder, and the like. As the other conductive agent, non-fibrous carbon materials are preferable, and carbon black is more preferable.

[0057] The content of the conductive agent in the positive electrode active material layer (total content of the fibrous carbon and other conductive agents) is preferably 1% by mass to 8% by mass, more preferably 2% by mass to 6% by mass, and even more preferably 3% by mass to 5% by mass. By setting the content of the conductive agent in the above range, it is possible to increase the energy density of the nonaqueous electrolyte storage element and further reduce the rate of increase in DC resistance after charge-discharge cycles.

[0058] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0059] The content of the binder in the positive electrode active material layer is preferably 0.3% by mass to 8.0% by mass, more preferably 0.5% by mass to 5.0% by mass, and even more preferably 1.0% by mass to 3.0% by mass. By setting the content of the binder in the above range, the positive electrode active material can be stably maintained.

[0060] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.

[0061] When the positive electrode active material layer contains a thickener, the content of the thickener in the positive electrode active material layer is preferably 0.1 mass% or more and 10 mass% or less, and more preferably 0.5 mass% or more and 8 mass% or less. The content of the thickener in the positive electrode active material layer may be 5 mass% or less, or may be 2 mass% or less. The technology disclosed herein may also be implemented in an embodiment in which the positive electrode active material layer does not contain a thickener.

[0062] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.

[0063] When the positive electrode active material layer contains a filler, the content of the filler in the positive electrode active material layer can be 0.1 mass% or more and 8 mass% or less, and usually, 5 mass% or less is preferable, and 2 mass% or less is more preferable. The technology disclosed herein can also be practiced in an embodiment in which the positive electrode active material layer does not contain a filler.

[0064] The positive electrode active material layer and the positive electrode mixture paste for forming the positive electrode active material layer may contain a neutralizing agent. When the content of an alkaline component such as lithium hydroxide that can be contained in the positive electrode active material is large, it may cause thickening of the positive electrode mixture paste. By including a neutralizing agent in the positive electrode mixture paste, thickening of the positive electrode mixture paste can be suppressed. As the neutralizing agent, for example, an organic acid such as a carboxylic acid can be used. The neutralizing agent may be present in the positive electrode active material layer in the form of a salt. In addition, when the purpose is only to suppress thickening of the positive electrode mixture paste, thickening is suppressed by using the neutralizing agent, so there is no need to reduce the content of lithium hydroxide in the positive electrode active material if the neutralizing agent is used. In the present invention, the content of lithium hydroxide in the positive electrode active material is reduced in order to reduce the rate of increase in direct current resistance after charge / discharge cycles as described above, as a purpose other than thickening of the positive electrode mixture paste.

[0065] The content of the neutralizer in the positive electrode active material layer may be, for example, from 0.01% by mass to 0.5% by mass, or from 0.02% by mass to 0.1% by mass.

[0066] The positive electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, fibrous carbon, and other conductive agents, binders, thickeners, fillers, and neutralizing agents.

[0067] <Method of manufacturing positive electrode for non-aqueous electrolyte storage element> A method for producing a positive electrode according to one embodiment of the present invention includes preparing a positive electrode mixture paste containing a positive electrode active material including a lithium transition metal composite oxide and fibrous carbon, wherein the lithium transition metal composite oxide contains at least one element selected from the group consisting of nickel, cobalt, and manganese, the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %, and the content of lithium hydroxide contained in the positive electrode active material is 0.20 mass % or less.

[0068] A method for manufacturing a positive electrode according to another embodiment of the present invention includes preparing a positive electrode mixture paste containing a positive electrode active material including a lithium transition metal composite oxide and fibrous carbon, wherein the lithium transition metal composite oxide contains at least one selected from the group consisting of nickel, cobalt, and manganese, the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %, and the content of lithium hydroxide contained in the positive electrode mixture paste is 0.20 mass % or less on a solids basis.

[0069] The positive electrode can be manufactured, for example, by applying the above-mentioned positive electrode mixture paste directly or through an intermediate layer to a positive electrode substrate, and drying to form a positive electrode active material layer. The positive electrode mixture paste usually contains other optional components and a dispersion medium in addition to the positive electrode active material and fibrous carbon. As the dispersion medium, an organic solvent such as N-methylpyrrolidone can be suitably used. The solid content in the positive electrode mixture paste refers to components other than the dispersion medium. That is, the content of lithium hydroxide contained in the positive electrode mixture paste is 0.20 mass% or less based on the solid content, which is synonymous with the content of lithium hydroxide in the solid content contained in the positive electrode mixture paste being 0.20 mass% or less. After drying, the positive electrode active material layer may be pressed or the like. The specific form of each component other than the dispersion medium, such as the positive electrode active material and fibrous carbon, contained in the positive electrode mixture paste is the same as the specific form of each component contained in the positive electrode described above.

[0070] <Non-aqueous electrolyte electricity storage element> A nonaqueous electrolyte storage element (hereinafter, also simply referred to as "storage element") according to one embodiment of the present invention includes an electrode assembly having a positive electrode, a negative electrode, and a separator, a nonaqueous electrolyte, and a container that contains the electrode assembly and the nonaqueous electrolyte. The electrode assembly is usually a laminated type in which a plurality of positive electrodes and a plurality of negative electrodes are laminated with a separator interposed therebetween, or a wound type in which a positive electrode and a negative electrode are laminated with a separator interposed therebetween and wound. The nonaqueous electrolyte exists in a state in which it is impregnated into the positive electrode, the negative electrode, and the separator. As an example of a nonaqueous electrolyte storage element, a nonaqueous electrolyte secondary battery (hereinafter, also simply referred to as "secondary battery") will be described.

[0071] (positive electrode) As the positive electrode, the above-mentioned positive electrode for the nonaqueous electrolyte storage element is used.

[0072] (Negative electrode) The negative electrode has a negative electrode substrate and a negative electrode active material layer disposed on the negative electrode substrate directly or via an intermediate layer. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode.

[0073] The negative electrode substrate has electrical conductivity. Metals such as copper, nickel, stainless steel, and nickel-plated steel, or alloys thereof, and carbon materials are used as the material of the negative electrode substrate. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0074] The average thickness of the negative electrode substrate is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate within the above range, it is possible to increase the strength of the negative electrode substrate and to increase the energy density per volume of the nonaqueous electrolyte storage element.

[0075] The negative electrode active material layer includes a negative electrode active material. The negative electrode active material layer includes optional components such as a conductive agent, a binder, a thickener, and a filler as necessary. The optional components such as the conductive agent, the binder, the thickener, and the filler can be selected from the materials exemplified for the positive electrode. The conductive agent used in the negative electrode active material layer may be either fibrous carbon or another conductive agent.

[0076] The negative electrode active material layer may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0077] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0078] "Graphite" refers to the average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0079] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0080] Here, the "discharged state" of the carbon material means a state in which the carbon material, which is the negative electrode active material, is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released from the carbon material, which is the negative electrode active material. For example, in a half cell using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, the open circuit voltage is 0.7 V or more.

[0081] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0082] "Graphitizable carbon" means the above d 002This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0083] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the negative electrode active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverizing method and the classifying method can be selected from, for example, the methods exemplified for the positive electrode. When the negative electrode active material is a metal such as metallic Li, the negative electrode active material layer may be in the form of a foil.

[0084] The content of the negative electrode active material in the negative electrode active material layer is preferably 60% by mass to 99% by mass, more preferably 90% by mass to 98% by mass. By setting the content of the negative electrode active material in the above range, both high energy density and manufacturability of the negative electrode active material layer can be achieved.

[0085] When the negative electrode active material layer contains a conductive agent, the content of the conductive agent in the negative electrode active material layer is preferably 1 mass% or more and 10 mass% or less, and more preferably 3 mass% or more and 9 mass% or less. The content of the conductive agent in the negative electrode active material layer may be 5 mass% or less, or may be 2 mass% or less. The technology disclosed herein may also be implemented in an embodiment in which the negative electrode active material layer does not contain a conductive agent.

[0086] When the negative electrode active material layer contains a binder, the content of the binder in the negative electrode active material layer is preferably 0.1% by mass to 10% by mass, more preferably 0.5% by mass to 8% by mass, and may be 6% by mass or less, or 4% by mass or less.

[0087] When the negative electrode active material layer contains a thickener, the content of the thickener in the negative electrode active material layer is preferably 0.1 mass% or more and 10 mass% or less, and more preferably 0.5 mass% or more and 8 mass% or less. The content of the thickener in the negative electrode active material layer may be 5 mass% or less, or may be 2 mass% or less. The technology disclosed herein may also be implemented in an embodiment in which the negative electrode active material layer does not contain a thickener.

[0088] When the negative electrode active material layer contains a filler, the content of the filler in the negative electrode active material layer can be 0.1 mass% or more and 8 mass% or less, and usually, 5 mass% or less is preferable, and 2 mass% or less is more preferable. The technology disclosed herein can also be practiced in an embodiment where the negative electrode active material layer does not contain a filler.

[0089] The negative electrode can be manufactured by a known method. The negative electrode can be manufactured, for example, in the same manner as the above-mentioned positive electrode manufacturing method, by applying a negative electrode mixture paste directly or via an intermediate layer to a negative electrode substrate, and drying the paste to form a negative electrode active material layer. After drying, the negative electrode active material layer may be pressed or the like.

[0090] (Separator) The separator can be appropriately selected from known separators. For example, a separator consisting of only a substrate layer, a separator in which a heat-resistant layer containing heat-resistant particles and a binder is formed on one or both surfaces of the substrate layer, etc. can be used as the separator. Examples of the shape of the substrate layer of the separator include woven fabric, nonwoven fabric, and porous resin film. Among these shapes, a porous resin film is preferred from the viewpoint of strength, and a nonwoven fabric is preferred from the viewpoint of non-aqueous electrolyte retention. As the material of the substrate layer of the separator, polyolefins such as polyethylene and polypropylene are preferred from the viewpoint of shutdown function, and polyimide and aramid are preferred from the viewpoint of oxidation decomposition resistance. A material obtained by combining these resins may be used as the substrate layer of the separator.

[0091] The heat-resistant particles contained in the heat-resistant layer preferably have a mass loss of 5% or less when heated from room temperature to 500°C under an air atmosphere at 1 atmosphere, and more preferably have a mass loss of 5% or less when heated from room temperature to 800°C. Examples of materials with a mass loss of a predetermined amount or less include inorganic compounds. Examples of inorganic compounds include oxides such as iron oxide, silicon oxide, aluminum oxide, titanium oxide, zirconium oxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicate; nitrides such as aluminum nitride and silicon nitride; carbonates such as calcium carbonate; sulfates such as barium sulfate; sparingly soluble ion crystals such as calcium fluoride, barium fluoride, and barium titanate; covalent crystals such as silicon and diamond; mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof. As the inorganic compound, these substances may be used alone or in the form of a complex, or two or more of them may be mixed and used. Among these inorganic compounds, silicon oxide, aluminum oxide, or aluminosilicate is preferred from the viewpoint of the safety of the nonaqueous electrolyte storage element.

[0092] The porosity of the separator is preferably 80% by volume or less from the viewpoint of strength, and is preferably 20% by volume or more from the viewpoint of discharge performance. Here, "porosity" refers to a volume-based value measured with a mercury porosimeter.

[0093] As the separator, a polymer gel composed of a polymer and a non-aqueous electrolyte may be used. Examples of the polymer include polyacrylonitrile, polyethylene oxide, polypropylene oxide, polymethyl methacrylate, polyvinyl acetate, polyvinylpyrrolidone, and polyvinylidene fluoride. The use of the polymer gel has an effect of suppressing leakage. As the separator, the above-mentioned porous resin film or nonwoven fabric may be used in combination with the polymer gel.

[0094] (Non-aqueous electrolyte) The nonaqueous electrolyte may be appropriately selected from known nonaqueous electrolytes. The nonaqueous electrolyte may be a nonaqueous electrolyte solution. The nonaqueous electrolyte solution includes a nonaqueous solvent and an electrolyte salt dissolved in the nonaqueous solvent.

[0095] The non-aqueous solvent can be appropriately selected from known non-aqueous solvents. Examples of the non-aqueous solvent include cyclic carbonates, chain carbonates, carboxylates, phosphates, sulfonates, ethers, amides, and nitriles. As the non-aqueous solvent, those in which some of the hydrogen atoms contained in these compounds are substituted with halogens may be used.

[0096] Examples of cyclic carbonates include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinylethylene carbonate (VEC), chloroethylene carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, 1-phenylvinylene carbonate, 1,2-diphenylvinylene carbonate, etc. Among these, EC is preferred.

[0097] Examples of the chain carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), diphenyl carbonate, trifluoroethyl methyl carbonate, bis(trifluoroethyl) carbonate, etc. Among these, EMC is preferable.

[0098] As the non-aqueous solvent, it is preferable to use a cyclic carbonate or a chain carbonate, and it is more preferable to use a combination of a cyclic carbonate and a chain carbonate. By using a cyclic carbonate, it is possible to promote dissociation of the electrolyte salt and improve the ionic conductivity of the non-aqueous electrolyte. By using a chain carbonate, it is possible to keep the viscosity of the non-aqueous electrolyte low. When using a cyclic carbonate and a chain carbonate in combination, it is preferable that the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate:chain carbonate) is, for example, in the range of 5:95 to 50:50.

[0099] The electrolyte salt can be appropriately selected from known electrolyte salts. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, onium salts, etc. Among these, lithium salts are preferred.

[0100] Examples of the lithium salt include inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, and LiN(SO2F)2, lithium oxalate salts such as lithium bis(oxalate)borate (LiBOB), lithium difluorooxalateborate (LiFOB), and lithium bis(oxalate)difluorophosphate (LiFOP), and lithium salts having a halogenated hydrocarbon group such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3. Among these, inorganic lithium salts are preferred, and LiPF6 is more preferred.

[0101] The electrolyte salt content in the non-aqueous electrolyte is 0.1 mol / dm at 20°C and 1 atmosphere. 3 More than 2.5mol / dm 3 It is preferable that the value is 0.3 mol / dm or less. 3 More than 2.0mol / dm 3 More preferably, it is 0.5 mol / dm or less. 3 More than 1.7mol / dm 3 More preferably, it is 0.7 mol / dm or less. 3More than 1.5mol / dm 3 By setting the content of the electrolyte salt within the above range, the ionic conductivity of the nonaqueous electrolyte can be increased.

[0102] The non-aqueous electrolyte may contain additives in addition to the non-aqueous solvent and the electrolyte salt. Examples of the additives include aromatic compounds such as biphenyl, alkylbiphenyl, terphenyl, partially hydrogenated terphenyl, cyclohexylbenzene, t-butylbenzene, t-amylbenzene, diphenyl ether, and dibenzofuran; partial halides of the aromatic compounds such as 2-fluorobiphenyl, o-cyclohexylfluorobenzene, and p-cyclohexylfluorobenzene; halogenated anisole compounds such as 2,4-difluoroanisole, 2,5-difluoroanisole, 2,6-difluoroanisole, and 3,5-difluoroanisole; vinylene carbonate, methylvinylene carbonate, ethylvinylene carbonate, succinic anhydride, glutaric anhydride, maleic anhydride, citraconic anhydride, glutaconic anhydride, itaconic anhydride, and cyclohexanedicarboxylic anhydride; ethyl sulfite; Examples of the additives include propylene sulfite, dimethyl sulfite, methyl methanesulfonate, busulfan, methyl toluenesulfonate, dimethyl sulfate, ethylene sulfate, sulfolane, dimethyl sulfone, diethyl sulfone, dimethyl sulfoxide, diethyl sulfoxide, tetramethylene sulfoxide, diphenyl sulfide, 4,4'-bis(2,2-dioxo-1,3,2-dioxathiolane), 4-methylsulfonyloxymethyl-2,2-dioxo-1,3,2-dioxathiolane, thioanisole, diphenyl disulfide, dipyridinium disulfide, 1,3-propene sultone, 1,3-propane sultone, 1,4-butane sultone, 1,4-butene sultone, perfluorooctane, tristrimethylsilyl borate, tristrimethylsilyl phosphate, and tetrakistrimethylsilyl titanate. These additives may be used alone or in combination of two or more.

[0103] The content of the additive contained in the non-aqueous electrolyte is preferably 0.01% by mass to 10% by mass, more preferably 0.1% by mass to 7% by mass, even more preferably 0.2% by mass to 5% by mass, and particularly preferably 0.3% by mass to 3% by mass. By setting the content of the additive within the above range, it is possible to improve the capacity retention performance or cycle performance after high-temperature storage, and to further improve safety.

[0104] The non-aqueous electrolyte may be a solid electrolyte, or a non-aqueous electrolyte solution and a solid electrolyte may be used in combination.

[0105] The solid electrolyte can be selected from any material that has ionic conductivity such as lithium, sodium, calcium, etc., and is solid at room temperature (e.g., 20° C.). Examples of the solid electrolyte include sulfide solid electrolytes, oxide solid electrolytes, nitride solid electrolytes, and polymer solid electrolytes.

[0106] As the sulfide solid electrolyte, in the case of a lithium ion secondary battery, for example, Li2S-P2S5, LiI-Li2S-P2S5, Li 10 Ge-P2S 12 etc.

[0107] The shape of the nonaqueous electrolyte storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a prismatic battery, a flat battery, a coin battery, and a button battery.

[0108] Fig. 1 shows a nonaqueous electrolyte storage element 1 as an example of a prismatic battery. The figure is a see-through view of the inside of the container. An electrode body 2 having a positive electrode and a negative electrode wound with a separator sandwiched therebetween is housed in a prismatic container 3. The positive electrode is electrically connected to a positive electrode terminal 4 via a positive electrode lead 41. The negative electrode is electrically connected to a negative electrode terminal 5 via a negative electrode lead 51.

[0109] <Electricity storage device> The nonaqueous electrolyte storage element of the present embodiment can be mounted as an electricity storage unit (battery module) comprising a plurality of nonaqueous electrolyte storage elements assembled together in automobile power sources such as electric vehicles (EVs), hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), etc., power sources for electronic devices such as personal computers and communication terminals, or power storage power sources, etc. In this case, the technology of the present invention may be applied to at least one of the nonaqueous electrolyte storage elements included in the electricity storage unit.

[0110] 2 shows an example of an electricity storage device 30 in which electricity storage units 20, each of which is an assembly of two or more electrically connected nonaqueous electrolyte electricity storage elements 1, are further assembled. The electricity storage device 30 may include a bus bar (not shown) that electrically connects two or more nonaqueous electrolyte electricity storage elements 1, a bus bar (not shown) that electrically connects two or more electricity storage units 20, and the like. The electricity storage unit 20 or the electricity storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more nonaqueous electrolyte electricity storage elements.

[0111] <Method of Manufacturing Nonaqueous Electrolyte Storage Element> The method for producing the nonaqueous electrolyte storage element of the present embodiment can be appropriately selected from known methods. The method for producing the nonaqueous electrolyte storage element of the present embodiment includes, for example, preparing an electrode body, preparing a nonaqueous electrolyte, and housing the electrode body and the nonaqueous electrolyte in a container. The preparation of the electrode body includes preparing a positive electrode and a negative electrode, and forming the electrode body by stacking or rolling the positive electrode and the negative electrode with a separator interposed therebetween.

[0112] The method of housing the non-aqueous electrolyte in the container can be appropriately selected from known methods. For example, when a non-aqueous electrolyte solution is used as the non-aqueous electrolyte, the non-aqueous electrolyte solution may be injected through an injection port formed in the container, and then the injection port may be sealed.

[0113] <Other embodiments> The nonaqueous electrolyte storage element of the present invention is not limited to the above-described embodiment, and various modifications may be made without departing from the scope of the present invention. For example, the configuration of one embodiment may be added to the configuration of another embodiment, and part of the configuration of one embodiment may be replaced with the configuration of another embodiment or a well-known technique. Furthermore, part of the configuration of one embodiment may be deleted. Also, a well-known technique may be added to the configuration of one embodiment.

[0114] In the above embodiment, the nonaqueous electrolyte storage element is used as a chargeable and dischargeable nonaqueous electrolyte secondary battery (lithium ion secondary battery), but the type, shape, size, capacity, etc. of the nonaqueous electrolyte storage element are arbitrary. The present invention can also be applied to various secondary batteries, electric double layer capacitors, lithium ion capacitors, and other capacitors.

[0115] In the above embodiment, the electrode assembly in which the positive electrode and the negative electrode are stacked with a separator interposed therebetween has been described, but the electrode assembly may not include a separator. For example, the positive electrode and the negative electrode may be in direct contact with each other in a state in which a non-conductive layer is formed on the active material layer of the positive electrode or the negative electrode. EXAMPLES

[0116] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0117] [Example 1] (Preparation of positive electrode) Positive electrode active material LiNi 0.6 Co 0.2 Mn 0.2A positive electrode mixture paste was prepared containing a lithium transition metal composite oxide represented by O2, carbon black (CB), CNT as fibrous carbon, a neutralizer, and polyvinylidene fluoride (PVDF) as a binder in a mass ratio (solid content equivalent) of 94.46:3.80:0.20:0.04:1.50, and N-methylpyrrolidone as a dispersion medium. The obtained positive electrode mixture paste was applied to the surface of an aluminum foil as a positive electrode substrate, and dried to prepare a positive electrode active material layer. Then, roll pressing was performed to obtain the positive electrode of Example 1. The content of lithium hydroxide (LiOH) contained in the positive electrode active material used was 0.08% by mass. From the composition of the positive electrode active material layer, the content of LiOH contained in the positive electrode active material layer of the obtained positive electrode was calculated to be 0.08% by mass.

[0118] (Preparation of negative electrode) A negative electrode mixture paste was prepared containing graphite as a negative electrode active material, styrene butadiene rubber (SBR) as a binder, and carboxymethyl cellulose (CMC) as a thickener in a mass ratio (solid content equivalent) of 96:3:1, with water as a dispersion medium. The obtained negative electrode mixture paste was applied to the surface of copper foil as a negative electrode substrate, and dried to prepare a negative electrode active material layer. Then, roll pressing was performed to obtain a negative electrode.

[0119] (Preparation of non-aqueous electrolyte) A non-aqueous solvent was prepared by mixing ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) in a volume ratio of 30:35:35. 3 A non-aqueous electrolyte was prepared by dissolving LiPF6 in the aqueous solution at a concentration of 1000 mM KOH.

[0120] (Assembly of non-aqueous electrolyte storage element) The positive electrode and the negative electrode were laminated with a polyethylene separator interposed therebetween to prepare an electrode assembly. The electrode assembly was placed in a container, and the nonaqueous electrolyte was poured into the container to obtain the nonaqueous electrolyte storage element of Example 1.

[0121] [Examples 2 to 4, Comparative Examples 1 to 3, Reference Examples 1 and 2] The positive electrodes and nonaqueous electrolyte storage elements of Examples 2 to 4, Comparative Examples 1 to 3, and Reference Examples 1 and 2 were obtained in the same manner as in Example 1, except that the type of lithium transition metal composite oxide as the positive electrode active material, the content of LiOH contained in the positive electrode active material, and the content of CB and CNT in terms of solid content in the positive electrode mixture paste (i.e., the content of CB and CNT in the obtained positive electrode active material layer) were as shown in Table 1 or Table 2. In addition, the content of LiOH in the positive electrode active material used was adjusted by appropriately changing the baking temperature and the degree of washing when producing the lithium transition metal composite oxide. Tables 1 and 2 also show the content (calculated value) of LiOH contained in the positive electrode active material layer.

[0122] [evaluation] (Initial charge / discharge) The obtained nonaqueous electrolyte storage elements were initially charged and discharged under the following conditions. In a thermostatic chamber at 25°C, constant current charging was performed with a charging current of 1.0C and a charge cut-off voltage of 4.20V, followed by constant voltage charging at 4.20V. The charge was terminated until the total charge time reached 3 hours. A rest period of 10 minutes was then provided. Constant current discharging was performed with a discharge current of 1.0C and a discharge cut-off voltage of 2.50V, and the initial discharge capacity was measured. (Initial DC resistance) Each nonaqueous electrolyte storage element after the initial charge and discharge was charged at a constant current of 1.0C in a thermostatic chamber at 25°C with a quantity of electricity of 50% of the initial discharge capacity, and the SOC was set to 50%. Then, in a thermostatic chamber at 25°C, the element was discharged for 30 seconds each at discharge currents of 0.2C, 0.5C, and 1.0C. After each discharge was completed, the element was charged at a constant current of 0.05C, and the SOC was set to 50%. The relationship between the discharge current at each discharge current and the voltage 10 seconds after the start of discharge was plotted, and the DC resistance was calculated from the slope of the straight line obtained from the plot of the three points, and was taken as the initial DC resistance.

[0123] (Charge-discharge cycle test) Next, the following charge-discharge cycle test was performed. In a thermostatic chamber at 45°C, constant current and constant voltage charging was performed with a charging current of 1.0C and a charge cut-off voltage of 4.20V. The charge was terminated until the total charge time reached 3 hours. Then, a rest period of 10 minutes was provided. A constant current discharge was performed with a discharge current of 1.0C and a discharge cut-off voltage of 2.50V, and then a rest period of 10 minutes was provided. For each of the nonaqueous electrolyte storage elements of the examples and comparative examples, the above charge-discharge cycle was performed 1,000 times. For each of the nonaqueous electrolyte storage elements of the reference examples, the above charge-discharge cycle was performed 500 times.

[0124] (Increase in DC resistance) After the charge-discharge cycle test, the DC resistance of each storage element was determined in the same manner as in the above "initial DC resistance" and was taken as the DC resistance after the charge-discharge cycle test. The increase rate of the DC resistance after the charge-discharge cycle test was calculated from the initial DC resistance and the DC resistance after the charge-discharge cycle test. The increase rate of the DC resistance (DCR increase rate) is shown in Tables 1 and 2.

[0125] [Table 1]

[0126] [Table 2]

[0127] As shown in Table 1, the nonaqueous electrolyte storage elements including the positive electrodes of Comparative Examples 1 and 2, which did not contain CNT, and Comparative Example 3, which contained CNT but had a high LiOH content, had a DCR increase rate of 30% or more after the charge-discharge cycle test. In contrast, the nonaqueous electrolyte storage elements including the positive electrodes of Examples 1 to 4, which contained CNT and had a low LiOH content, had a DCR increase rate of less than 30% after the charge-discharge cycle test, and the DCR increase rate was reduced. As shown in Table 2, in Reference Examples 1 and 2 using lithium transition metal composite oxides in which the content of nickel element relative to all metal elements other than lithium element is 80 mol % or more, Reference Example 1, which has a lower LiOH content, showed a higher DCR increase rate despite the higher CNT content. The reason for this is presumably that lithium transition metal composite oxides in which the content of nickel element relative to all metal elements other than lithium element is 80 mol % or more usually contain LiOH in an amount significantly exceeding 0.20 mass %, so excessive calcination or washing with water is required to reduce the LiOH content to 0.20 mass % or less, which changes the crystal structure and causes a decrease in performance. [Industrial Applicability]

[0128] The present invention can be applied to nonaqueous electrolyte electricity storage elements used as power sources for electronic devices such as personal computers and communication terminals, and automobiles. [Explanation of symbols]

[0129] 1. Non-aqueous electrolyte storage element 2 Electrode body 3 containers 4 Positive terminal 41 Positive lead 5 Negative terminal 51 Negative lead 20 Energy Storage Unit 30 Energy storage device

Claims

1. A positive electrode active material layer containing a positive electrode active material including a lithium transition metal composite oxide and fibrous carbon, the lithium transition metal composite oxide contains at least one element selected from the group consisting of nickel, cobalt, and manganese, and the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %; The positive electrode for a nonaqueous electrolyte storage element, wherein the content of lithium hydroxide contained in the positive electrode active material is 0.20 mass % or less.

2. A positive electrode active material layer containing a positive electrode active material including a lithium transition metal composite oxide and fibrous carbon, the lithium transition metal composite oxide contains at least one element selected from the group consisting of nickel, cobalt, and manganese, and the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %; The positive electrode for a nonaqueous electrolyte storage element, wherein the content of lithium hydroxide contained in the positive electrode active material layer is 0.20 mass % or less.

3. The method includes preparing a positive electrode mixture paste containing a positive electrode active material including a lithium transition metal composite oxide and fibrous carbon; the lithium transition metal composite oxide contains at least one element selected from the group consisting of nickel, cobalt, and manganese, and the content of the nickel element relative to all metal elements other than lithium in the lithium transition metal composite oxide is less than 80 mol %; The method for producing a positive electrode for a nonaqueous electrolyte storage element, wherein the content of lithium hydroxide contained in the positive electrode active material is 0.20 mass % or less.

4. A non-aqueous electrolyte storage element comprising the positive electrode for a non-aqueous electrolyte storage element according to claim 1 or 2.

Citation Information

Patent Citations

  • Positive electrode active material for lithium secondary battery, positive electrode and secondary battery

    JP2015018678A

  • Lithium ion secondary battery

    WO2019088171A1